Synthesis of Chitosan Oligomers/Propolis/Silver Nanoparticles Composite Systems and Study of Their Activity against Diplodia seriata - Petruta Mihaela Matei; Pablo Martín-Ramos; Mercedes Sánchez-Báscones; Salvador Hernández-Navarro; Adriana Correa-Guimaraes; Luis M. Navas-Gracia; Cassyo Araujo Rufino; M. Carmen Ramos-Sánchez; Jesús Martín-Gil (International Journal of Polymer Science)
The synthesis and characterization of composites of oligomeric chitosan with propolis extract which allow the incorporation of a third component (silver nanoparticles) are reported, together with their application in aqueous or hydroalcoholic solutions with a view to the formation of adhesive substances or nanofilms for the protection of vineyards against harmful xylophagous fungi. The antimicrobial properties of the association of the two biological products or those resulting from the incorporation of silver nanoparticles (NPs) are studied and discussed. The efficacy of the chitosan oligomers/propolis/silver NPs ternary system is assessed in vitro for Diplodia fungi. A preliminary study on the convenience of replacing propolis with gentisic acid is also presented.